Selection of Trichogramma species for controlling the Diamondback moth - Pratissoli,Dirceu (2008)
Biological characteristics of the egg parasitoids Trichogramma acacioi, T. atopovirilia, and T. bennetti were studied to select the one with better performance on the control of the Diamondback moth, Plutella xylostella. Parasitism rate, viability, and sex ratio were studied. Parasitism rate ranged from 1.67 to 41.33%. T. atopovirilia and T. acacioi were respectively the most and less aggressive species. The viability ranged from 6.20% for T. acacioi to 53.34% for T. atopovirilia. There were no differences on sex ratio (P < 0.05) that remained above 0,88. T. atopovirilia was the species with best performance in the laboratory when rearing on the Diamondback moth eggs.